Special Issue “Natural Language Engineering: Methods, Tasks and Applications” - Massimo Esposito; Giovanni Luca Masala; Aniello Minutolo; Marco Pota (Future Internet, 2022)
Natural language engineering includes a continuously enlarging variety of methods for solving natural language processing (NLP) tasks within a pervasive number of applications [...]